Effect Analysis on Coating Methods and Corrosive Media Variations toward Adhesion Strength, Corrosion Rate, and Metallography of ASTM A36 Steel with Polyurethane Coating - Herman Pratikno; Inaya Krista Pradyptia; Hasan Ikhwani (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2021)
Corrosion can cause material damage due to the material’s reaction with the environment. Corrosion will affect materials on construction, including metal material, thereby reducing the strength and the construction life, especially in a corrosive environment. The most effective and economical corrosion control is coating. The right coating application method will result in good bonding of the paint with the material, so that the corrosion protection will be better. This research used the ASTM A36 carbon steel material and polyurethane coatings. The purpose of this study is to determine the adhesion strength and corrosion rate by varying the application methods, namely brush, roll, and spray. In the pull-off test, the highest value of adhesion strength was obtained in the spray coating method with an average value of 20,82 MPa. Whereas in the three-electrode cell testing, the lowest corrosion rate using NaCl corrosive media was found in the spray coating method with a value of 0.000025402 mmpy and the lowest corrosion rate using FeCl3 corrosive media was found in the spray coating method with a value of 0.00182 mmpy.